Fruit yogurt: Any erosive potential regarding teeth? - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2006)
Objective: The capability of drinks and foods to resist pH changes brought about by salivary buffering may play an important role in the dental erosion process in children. The aim of the present study was to test fruit yogurt, a popular snack for children, and the degrees of saturation (pK-pl) with respect to hydroxyapatite and fluorapatite to determine their erosive potential. Method and Materials: A variety of fruit yogurt was tested. To test the pH, 8 readings were taken with a pH electrode for each yogurt. Calcium content was detected by atomic absorption spectrophotometer, phosphorus by the inductively coupled plasma method, and fluoride content by ion chromatography. The degrees of saturation of hydroxyapatite and fluorapatite were calculated by use of a computer program. Statistical analysis was performed using 2-tailed analysis of variance (P < .05) and a post hoc test (Tukey) to determine differences between groups. Results: The pH of each fruit concentrate was significantly different, except for banana yogurt. Except for the phosphorus content of raspberry yogurt, the calcium and phosphorus content for each fruit concentrate were significantly different. Fluoride levels were the same for all yogurts tested, and the degrees of saturation of hydroxyapatite and fluorapatite was positive, indicating supersaturation. Conclusion: It could be stated that fruit yogurt has no erosive potential.
Keywords: dental erosion; fluorapatite; fruit yogurt; hydroxyapatite; DENTAL EROSION; ENAMEL EROSION; MILK-PRODUCTS; SOFT DRINKS; SOLUBILITY; BEVERAGES; HEALTH; PH